2022
DOI: 10.18502/cjn.v21i3.11112
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, hypertension, smoking, and hyperlipidemia as risk factors for spontaneous cervical artery dissection: Meta-analysis of case-control studies

Abstract: Background: Spontaneous cervical artery dissection (sCeAD) is an important cause of ischemic stroke in the young population and has a different cardiovascular risk profile from other causes of ischemic stroke. No study provided a comprehensive evidence for cardiovascular risk factors of sCeAD. Methods: We searched PubMed, MEDLINE, and Embase without date or language restrictions for relevant studies. Bibliographies of included studies were also searched. We included case-control studies where patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Most of our findings, particularly on the relationship between traditional cardiovascular risk factors and sCeAD, are substantially in line with those of the only observational study conducted so far, including a large series of patients with sCeAD (which partly overlaps with the present one), a group of patients with non‐CeAD IS and a group of stroke‐free control subjects, 12 as well as with those of other smaller studies 3,13–15 . Overall, these results underscore a neutral or inverse association of classic pro‐atherosclerotic risk factors with disease risk in comparison with the 2 control groups, with the only notable exception of hypertension, which is confirmed in our analysis as a major susceptibility factor for sCeAD 3 . Similarly, the hypothesis of a link between migraine and sCeAD, based on the results of 2 previous large studies 16,17 and a few other smaller ones, 18 is essentially confirmed by the results of the present analysis.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Most of our findings, particularly on the relationship between traditional cardiovascular risk factors and sCeAD, are substantially in line with those of the only observational study conducted so far, including a large series of patients with sCeAD (which partly overlaps with the present one), a group of patients with non‐CeAD IS and a group of stroke‐free control subjects, 12 as well as with those of other smaller studies 3,13–15 . Overall, these results underscore a neutral or inverse association of classic pro‐atherosclerotic risk factors with disease risk in comparison with the 2 control groups, with the only notable exception of hypertension, which is confirmed in our analysis as a major susceptibility factor for sCeAD 3 . Similarly, the hypothesis of a link between migraine and sCeAD, based on the results of 2 previous large studies 16,17 and a few other smaller ones, 18 is essentially confirmed by the results of the present analysis.…”
Section: Discussionsupporting
confidence: 88%
“…3,[13][14][15] Overall, these results underscore a neutral or inverse association of classic proatherosclerotic risk factors with disease risk in comparison with the 2 control groups, with the only notable exception of hypertension, which is confirmed in our analysis as a major susceptibility factor for sCeAD. 3 Similarly, the hypothesis of a link between migraine and sCeAD, based on the results of 2 previous large studies 16,17 and a few other smaller ones, 18 is essentially confirmed by the results of the present analysis. Notwithstanding, our study represents a substantial step forward compared to previous analyses and some of their inherent methodological limitations.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…In the first meta‐analysis we compared 2185 patients with CeAD and 3185 healthy controls. 3 There was a significant association of CeAD with hypertension and no association with smoking or diabetes. There was a negative association with hyperlipidaemia but sensitivity analysis with inclusion of studies that only compared total cholesterol between the CeAD and control groups showed no statistical association.…”
mentioning
confidence: 89%
“…Many environmental and genetic risk factors have been proposed such as α1‐antitrypsin deficiency, hyperhomocysteinemia, recent infection, connective tissue disorders, styloid process length, and arterial tortuosity. 3 Few studies specifically addressed the link of CeAD with cardiovascular risk factors. In the Cervical Artery Dissections and Ischemic Patients (CADISP) group, which is a large international multicentre registry, the prevalence of smoking, diabetes and hypertension were statistically lower in CeAD than in non‐dissection ischemic stroke.…”
mentioning
confidence: 99%